(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2026)
The southern coasts of the Mediterranean Sea suffer from a notable lack of scientific studies compared to the northern coasts, leading to a significant knowledge gap in understanding environmental changes in the region. The coast of Tocra in Libya represents a clear example of this deficiency, despite its environmental and economic importance. This review compiles and analyzes data collected between 2015 and 2024 from various sources, including peer-reviewed scientific research, official reports, and field observations, using a systematic approach that incorporates physical and chemical parameters, biological indicators, and human activities to track environmental trends. The results indicate that the Tocra coast is undergoing considerable environmental degradation, with nitrate concentrations increasing by 35.2% (p < 0.05) and phosphate levels by 28.7% (p < 0.05), while dissolved oxygen in near-bottom waters decreased by 18.3%. Biologically, Posidonia oceanica coverage declined by 42.6%, demersal fish diversity by 51.8%, and sensitive benthic species by 63.4%, whereas opportunistic species increased by 38.9%. These findings reveal that the Tocra coast is experiencing accelerated degradation driven by eutrophication, habitat destruction, and climate change. Immediate interventions are urgently required, including the implementation of Integrated Coastal Zone Management, establishment of Marine Protected Areas, and enhancement of monitoring systems to mitigate further irreversible environmental damage.